(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Now-a-days the extensible Markup Language (XML) is also become essential in geographic information systems (GIS). To assist this demand, the OpenGis Consortium proposed the GML (Geography Markup Language), a markup language for specify geographical information, including space properties. One may understand GML as a collection of various geometric properties, objects to describe coordinate reference systems, a topology, specific time, measurement units and generic values. This scientific language agrees to describe the data by using of basic models which are published as per the OpenGis specifications. It applies the XML pattern and possesses the methods and principles to describe geographical information. This paper reveals a novel approach to store GML documents in object-relational database management systems. It also makes an analysis of the renovations of a repository and GML metadata for object-relational database management system.